Chemical inhibition of xylem cellular activity impedes the removal of drought‐induced embolisms in poplar stems – new insights from micro‐CT analysis. Issue 2 (29th September 2020) - Secchi, Francesca; Pagliarani, Chiara; Cavalletto, Silvia; Petruzzellis, Francesco; Tonel, Giulia; Savi, Tadeja; Tromba, Giuliana; Obertino, Maria Margherita; Lovisolo, Claudio; Nardini, Andrea; Zwieniecki, Maciej A.
Summary: In drought‐stressed plants a coordinated cascade of chemical and transcriptional adjustments occurs at the same time as embolism formation. While these processes do not affect embolism formation during stress, they may prime stems for recovery during rehydration by modifying apoplast pH and increasing sugar concentration in the xylem sap. Here we show that in vivo treatments modifying apoplastic pH (stem infiltration with a pH buffer) or reducing stem metabolic activity (infiltration with sodium vanadate and sodium cyanide; plant exposure to carbon monoxide) can reduce sugar accumulation, thus disrupting or delaying the recovery process. Application of the vanadate treatment (NaVO3, an inhibitor of many ATPases) completely halted recovery from drought‐induced embolism for up to 24 h after re‐irrigation, while partial recovery was observed in vivo in control plants using X‐ray microcomputed tomography. Our results suggest that stem hydraulic recovery in poplar is a biological, energy‐dependent process that coincides with accumulation of sugars in the apoplast during stress. Recovery and damage are spatially coordinated, with embolism formation occurring from the inside out and refilling from the outside in. The outside‐in pattern highlights the importance of xylem proximity to the sugars within the phloem to the embolism recovery process.